Analisis Keefektifan Kalimat dalam Teks Eksposisi Bertema Gaya Hidup Sehat pada Portal Kesehatan Daring alodokter.com Edisi Januari-Juni 2024 sebagai Edukasi Kesehatan Publik - Azzahra Nabila; Ela Indriyani; Citra Resti Anggriani; Sayka Absa Azzahra; Aisyah Salsha; Asep Purwo Yudi Utomo; Fahrudin Eko Hardijanto; Ryan Hidayat (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Health education important role in raising public awareness of health, particularly in adopting a healthy lifestyle. With the advancement of digital technology, online health portals such as alodokter.com have become key sources of health information. To ensure effective message delivery, the sentences in expository texts must be clear, concise, and easily understood, preventing any misinterpretation by the public as the readers. Therefore, this study aims to analyze the effectiveness of sentences in expository text on a healthy lifestyle published on alodokter.com from January-June 2024 as part of public health education efforts. The effectiveness of sentences is assessed based on several aspects, including structure and grammar, word choice, clarity of information and readability for the general public. This research employes a qualitative descriptive approach and a syntactic approach as its theoretical framework. Data collection techniques involve the observe and note method. Data analysis is conducted using the distributional method (agih technique) to examine syntactic structure and sentence coherence, as well as the referential method (padan technique) to evaluate meaning clarity and reads comprehension. The research process is carried out in three steps: (1) data collection, (2) data analysis, and (3) presentation of research findings. The research object consists of expository text on online health portals discussing healthy lifestyles. Several articles are selected and analyzed in depth. The data presentation technique in this research uses formal and informal methods. The analysis result reveal the ineffectiveness of several sentences in the expository texts, particularly in terms of their inconsistency with the characteristics of effective sentences, such as unity, coherence, emphasis, and conciseness. The result of this study contribute to a deeper comprehension of the topic being explored. Furthermore, the study is beneficial for the public as a form of health education and awareness.